KEMAMPUAN MENULIS PUISI SISWA KELAS VII SMP NEGERI I LEMBAH GUMANTI KABUPATEN SOLOK DENGAN MENGGUNAKAN TEKNIK MENEMUKAN (INQUIRY) - Rulando, Citra; Mana, Lira Hayu Afdetis; Nisja, Indriani (Pendidikan Bahasa Indonesia, 2013)
This study aims to describe the ability of grade VII Junior Home Affairs I Gumanti Valley in poetry. Type of this research is quantitative research using descriptive method. The population is grade VII Junior Home Affairs I Valley Gumanti years lessons 2012-2013. A sample of these studies amounted to 30 people with a proportional random sampling techniques. Research data is text poem written students based on two indicators: diction, and majo. Based on the analysis of the data shows that, first, the ability to write poetry class VII students of SMP Negeri Solok Regency Gumanti Valley I by using the techniques found (inquiry) for indicators of diction is good (B) with the means to become rounded 83,3 83 found on the stretch of 76-85%.Â  Second, the ability to write poetry Class VII students of SMP Negeri Solok Regency Gumanti Valley I by using the techniques found (inquiry) to Majo indicator is more than enough (LDC) and to rounded 69,3 69 means in the range of 65-75%. Third, the ability to write poetry Class VII students of SMP Negeri Solok Regency Gumanti Valley I by using the techniques found (inquiry) is a good indicator for the second (B) with the means to become rounded 76,3 76 found on the stretch of 76-85%.Relevant to the case, the researchers put forward several suggestions, which are as follows. First, in order for the students classes VII Junior Home Affairs I Valley Gumanti more reading material related to poetry so as to increase knowledge and enrich the diction in poetry. Second, subjects that teachers of language and literature in junior high Country Indonesia I Gumanti Valley further enhance learning technique variation in poetry. Third, that teachers of subjects language and literature in junior high Country Indonesia I Valley Gumanti more poetry writing exercise that gives students more skillfully and creatively in terms of writing poetry.